A comparative study of locking plate by minimally invasive percutaneous plate osteosynthesis versus closed interlocking intramedullary nail in extra-articular distal tibia fractures - Chitten, Jojin Jose; Balasubramaniam, R. (International Journal of Research in Orthopaedics, 2021)
Background: To compare functional outcome between minimally invasive percutaneous plate osteosynthesis (MIPO) and intramedullary interlocking nail (IMIL) in the distal one-third extra-articular tibia fracture. Methods: We retrospectively analysed 32 patients with closed distal tibia extra-articular fractures who underwent IMIL nail and locking plate MIPO technique in 16 patients each. All patients were followed for at least one year with assessment of clinico-radiological union and functional outcome scoring. Results: There was comparable functional outcomes, time to union and surgical time both in IMIL nail and MIPO fixation of closed distal extra-articular tibia fractures with similar complication rate. Conclusions: Our study suggests that both IMIL nail and MIPO fixation could be used for closed distal extra-articular tibia fractures as per surgeon’s preference. However, due to small sample size in our study, we cannot draw any definitive conclusions from our preliminary results but consider them as valuable basis for future studies.